PROGRAM PEMBERDAYAAN MASYARAKAT BERBASIS MANAJEMEN MASJID - Romhan Romhan; Agus Zainal Rachmat; Sofino Sofino (Jurnal Pendidikan Sepanjang Hayat, 2020)
The purpose of this study is to find out empowerment and community programs in the Baitul Atieq Great Mosque which is a mosque with the Jami mosque's typology. This study refers to indicators of success according to the Decree of the Director General of Islamic Community Guidance in 2014 concerning Standards for Management of Mosque Management. This research is a qualitative case study with four research subjects and data collection techniques using interview, observation and documentation techniques. While data analysis techniques include data reduction, data presentation, and drawing conclusions. Checking the validity of the data using triangulation ranging from time triangulation, subject triangulation and technique triangulation. The results showed that the community empowerment programs carried out at the Baitul Atieq Great Mosque covered the fields of education, da'wah, social and economic, besides the existing programs involved all parties and covered community needs. Keywords: Program, Empowerment, Mosque